Consciousness and Absolute. Subjectivity and objectivity between Bergsonian philosophy and Indian thought (Nóema, 2012)
Moving by a theoretic approach, the paper intends to think through the connections between the Indian philosophy of Śaṃkara (the greater thinker of the Vedanta school, lived in the VIII century b. C.) and the thought of H. Bergson. By such a prospective, indeed, becomes possible a critical remark about some problems of interpretation of the thought of both the authors, who – as we shall see – share a common conceptual horizon.
Keywords: samkara; bergson; indian philosophy; vedanta; consciousness; absolute; élan vital; creative evolution; matter; image